Health nutrition and economic development. - Strauss, John; Thomas, Duncan (Journal of Economic Literature, 1995)
The relationship between economic development and health has received far less attention than the relationship between development and schooling. However, recent studies indicate that better health is associated with improved labor market outcomes, particularly in low-income settings. Difficulties in disentangling the causal mechanisms underlying these associations are discussed, highlighting the role of behaviors and measurement of health. The empirical literature is reviewed, and implications of results for the functioning of markets are drawn out. The discussion includes an evaluation of the empirical evidence in support of the nutrition (health) efficiency wage hypothesis: we conclude that it is thin.